ADAPTIVE WEB INFORMATION EXTRACTION. - Gregg, Dawn G.; Walczak, Steven (Communications of the ACM, 2006)
An analysis of the Amorphic System of Web information management is presented. The author reviews how Web mining has the potential to dramatically change in the way individuals access and use the information available on the Internet. The author discusses the emergence of Web business support software applications. It is suggested that Web information services and Web business intelligence applications should be structured in such a way as to incorporate their value-added services. The benefits of Adaptive Information Extraction Systems are analyzed.